Visual aesthetics of narrative animation of 3D computer graphics: From both realist and expressive points of view - Wibowo, Mars Caroline; Nugrhono, Sarwo; Wibowo, Agus (Humanities, Arts and Social Sciences Studies, 2024)
The field of animation is a unique realm for artistic creativity to convey stories. Animation is a technique in which images are manipulated to display moving visuals. In traditional animation, images are painstakingly hand-drawn or painted on transparent celluloid sheets, which are then photographed and showcased on film. The process of creating 3D animation is highly intricate and time-consuming. Animators must consider numerous factors to produce high-quality, visually stunning animation. The current study aligns with the ongoing development in computer graphics, which are influenced by the hyper-realist ethos. The study delves into animation aesthetics, computer graphics technology, and culture within the realm of 3D animation. For comparison, it also presents the findings of researchers and computer graphics experts, focusing on more expressive 3D narrative animations. This study merges research in art history, computer graphics, psychology, and expressive visual style, particularly their naturalistic attributes and emotional engagement. Regarding the potential for natural expression, this study draws upon two fundamental aspects of 3D technology: photorealistic rendering and one-point perspective. It is expected that future technological advancements will further enhance the evolution of expressive aesthetics in 3D animation. In conclusion. this study emphasizes that future 3D animation creation should prioritize aesthetic expressiveness.